Fundamentals Of Entrepreneurship (ENT300) : Love + Brownies Enterprise / Sabreena Wam ... [et al.] - Wam, Sabreena; Sa'adan, Azlin; Azlan, Nurul Faezah (2017)
Love Y Brownies is a bakery-concept shop that only sells brownies. However, Love + Brownies will offer a vañety of brownies. The name of Love Brownies is coming from cur passion of baking pastry, We decide to only focus on brownies of the opponunity that exists in the business. Our team strives to bring happiness and excitement to the life ofour customers. Love + Brownies will be located at Kota Samaràhan due to strengths and the opportunity in the area. Our team at Love + Brownies plan to manipulate our location to our utmost advantage. Our target customers are young adults and adults due to the facilities in Kota Samarahan. The weakness and threats that exists in this business can be overcome with a great strategy by our team at Love + Brownies.